Blood profile of red sokoto bucks fed diets containing varying levels of yam peel meal with Ficus polita as basal diets - Oloche, J.; Kume, A.B.; Ayoade, J.A. (Nigerian Journal of Animal Science, 2023)
Sixteen (16) Red Sokoto bucks with an average weight of 9.11 kg and aged 6 - 8 months were used to assess the blood profile of Red Sokoto goats fed diets containing high levels of yam peels with Ficus polita as basal diets in a completely randomized design (CRD). Yam peels were collected from food vendors from markets within Makurdi Metropolis, it was sun-dried for 3days and crushed into a meal using mortar and pestle. This was used to compound four experimental diets designated D1 (0%), D2 (50%), D3 (75%) and D4 (100%) Yam Peel Meal (YPM) and were used to feed the Red Sokoto bucks for 105 days. Results obtained from this study shows that there was no effect of treatment (P>0.05) on the haematological parameters measured. Similarly, mean values of serum biochemistry parameters assayed did not show treatment effect (P>0.05). The total protein value of D1 (5.28mg/dl) was significantly lower (P<0.05) than those of D2 (7.93(mg/dl), D3 (7.33mg/dl)) and D4 (7.68(mg/dl). However, there was no statistical difference (P>0.05) in the total protein values of D2, D3 and D4. The serum minerals measured (calcium, potassium, sodium, phosphorus, magnesium and chloride) were similar (P>0.05) across the treatments. Cost analysis of treatments showed that none of treatments resulted in loss, but treatment D2 appears to have the best profit margin. The study shows that YPM can be used to replace maize offal up to 100% without compromising the health of the goats and enhance profitability of the goat enterprise.